Analisis Rasio Keuangan Sebagai Penilaian Kinerja Keuangan Perum Bulog Sub Divisi Regional Wilayah IV Maumere - Magdalena Silaswati Samosir; Henrikus Herdi; Emilianus Eo Kutu Goo; Paulus Libu Lamawitak (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to provide information about the financial performance of Perum Bulog Regional Sub Division IV Maumere in 2017-2019. The analysis was carried out by comparing the financial ratios of Perum Bulog Regional Sub Division IV Maumere with industry standards based on Kasmir. The financial ratios used are: Current Ratio, Quick Ratio, Debt To Asset Ratio, Debt To Equity Ratio, Net Profit Margin, Return On Investment, Return On Equity, and Total Asset Turnover. This research uses descriptive quantitative research methods. The calculation results show that the company's liquidity ratios in the form of current ratios and quick ratios have good financial performance. The average solvency ratio is below the industry standard and is in the good category, while in 2019 it is in the poor category because it is above the industry standard. Financial performance based on the profitability ratios reviewed using net profit margin is in poor condition, reviewed using return on investment has good financial performance because it is above standard, while in 2019 financial performance is not good because it is below standard, and reviewed using return on equity financial performance is good. Financial performance based on the company's activity ratio is in good condition, while in 2019 the company's condition is not good Keywords: Financial Ratios, Financial Reports, Financial Performance